(3GdecJHI GdeOQSjI GdeWhQIs - (3GdfGJhJ, gdGds ((3HjQhJs (3OGQ GdfgVI GdYQHjIs, 2002)
(3jTJed gPG GdcJGH Ydi KdGKI eMGhQ QFjSjI fXQjI hCcGOjejI hJbfjI aj KeGfjI aUhd eJdGMbI JOhQ Mhd GdecJHI GdeOQSjI GdeJWhQI(B. (3Ve GdeMhQ GdChd(B: (3GdEWGQ GdfXQj ddecJHI hOhQgG GdbQGFj hehGUaGJgG ef CLd GdUMI GdfaSjI Ke JfXjeGJgG GdEOGQjI hLGA Pdc aj KdGKI aUhd(B. (3aj GdaUd GdChd JfGhd GdGSJYOGOGJ GdbQGfjI heQGMd Gdfeh ddEfSGf dJOGNd HYVgG HYVkG hJHGOd JCKjQgG HeG GSJhLH Ydi GdeDda PcQ CgOGa GdbQGAI hCfhGYgG(B. (3hYQV aj GdaUd GdKGfj GdTQhW GdhGLH JhGaQgG dehGUaGJ GdecJHI GdeOQSjI dLgI aVGAJ eSGMGJgG hJbSjeGJgG, hGdCKGK hGdJLgjRGJ GddGReI MSH ebGjjS GdEadG (BIfla (3GdYGdejI, aVdkG Yf VQhQI JhGaQ JcfhdhLjG GdeYdheGJ(B. (3CeG GdaUd GdKGdK aJfGhd eSCdI GdJfXje GdEOGQj ddecJHI hehGRfJgG hPdc deG jJWdHg EOGQI GdecJHI ef EOGQI aGYdI YHQ MSf GdETQGa hGdeJGHYI dYed Gdafjjf ajgG, Ke cGf GdeMhQ GdKGfj(B: (3hgh GdEWGQ GdCcGOjej dYed GdecJHI Hd gh GdgOa ef JCSjSgG hJhXja eQOhOgG ddYed GdJQHhj GdeOQSj ddCSGJPI hGdWdGH eYkG, hVe GdeDda aj gPG GdeMhQ KdGKI aUhd(B. (3JMOK aj GdChd Yf CgOGa GdecJHI GdeOQSjI hCfhGYgG aj TJi eQGMd GdOQGSI hHGdJGdj JfGhd eSCdI hXGFagG GdCcGOjejI hZjQ GdCcGOjejI, eeKdkG HGdecJHI GdTGedI cfehPL Mj Ydi Pdc(B. (3haj GdaUd GdKGfj JMOK Yf eSCdI JWHjb GdCgOGa GdSGHbI YHQ cjajI JOQjH GdWdGH Ydi GdJQHjI GdecJHjI dLgI CZQGVgG heaghe efgLgG, ebOekG JWHjbGJ fehPLjI YedjI deNJda eQGMd GdOQGSI(B. (3CeG GdaUd GdKGdK aVefg OQGSI ddHYO GdJQHhj GdMbjbj ddecJHI GdeOQSjI(B. (3hCNjQkG GdeMhQ GdKGdK hgh GdEWGQ GdJbfj dOhQ GdecJHI GdeJeKd aj NOeGJgG Ydi GdUYjO GdOQGSj GdKbGaj hUhQ GdYedjGJ GdafjI HOGNdgG hVefgG aUdGf(B: (3GdChd JMOK ajg NOeGJ GdecJHI GdeOQSjI GdeJfhYI eKd GdEYGQI(B... (3CeG GdKGfj hGdNjQ aVefg GdYedjGJ GdafjI hGdJbfjI GdJj JJe YGOI aj Cj ecJHI hGdeJeKdI aj GdagQSI GdhUajI hGdehVYjI hGdJUfja GdecJHj heHGOFg, aGdGbJfGA hGdJRhjO hVQhQI JQJjH GdMhGQ hUjGZJgG(B. (3hRjGOI aj EjVGM ehGO GdcJGH CJHY GdeDda cJGHI edMbjf Vef GdChd agekG edNUkG Yf fOhI YbOJ aj GdChfjSch Mhd GdecJHI GdeOQSjI aj dHfGf, CeG GdKGfj aVefg ebJQM JhLjgj ddecJHGJ GdeOQSjI hJUfja Ojhj GdeYqOd ddecJHI GdeOQSjI GdYQHjI hPcQ ddGJMGO GdYQHj ddecJHGJ(B.s
(3GdfhY (B: (3cJGHs
Keywords: Librairie Scolaire; School Library; (3GdeOQSjIs; (3GdecJHIs